A single molecule raman detection test strip and method of use
By depositing Au@Ag NPs clusters in the test strip cartridge and combining a spiral injector and a tilting test strip groove, the fluid velocity and molecular enrichment are optimized, solving the problems of complex preparation and high cost in the prior art. This achieves highly sensitive single-molecule detection, which is suitable for the detection of practical samples.
Patent Information
- Application Number
- CN202311158349.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2026-07-03
- Estimated Expiration
- 2043-09-08
AI Technical Summary
Existing surface-enhanced Raman scattering substrate technology suffers from complex preparation, high cost, low sensitivity, and difficulty in achieving single-molecule detection. Liquid chromatography-mass spectrometry (LC-MS) methods are characterized by high instrument maintenance costs, complex operation, and low efficiency, making them difficult to widely apply in practical detection.
Au@Ag NPs clusters were deposited on the paper tip of the test strip using a polymer-assisted printing method. Combined with a spiral sampler and a tilted test strip groove, fluid velocity and molecular enrichment were optimized to achieve directional enrichment of micro hotspots and improve macroscopic performance.
It achieves single-molecule level detection with a detection limit of 10⁻⁹ M, high sensitivity, simple and easy-to-operate structure, low cost, and is suitable for detection of practical samples.
Smart Images

Figure CN117054394B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of single-molecule detection technology, and in particular relates to a single-molecule Raman detection test kit and its usage method. Background Technology
[0002] Single-molecule detection is a rapidly developing ultrasensitive detection technology that has shown great promise in the quantitative detection of small molecules and biomolecules over the past decade. Currently, liquid chromatography-mass spectrometry (LC-MS) is commonly used for molecular detection due to its wider applicability, high sensitivity, and high throughput, meeting the qualitative and quantitative requirements of various fields. However, LC-MS, as a high-precision instrument, has a complex structure, high maintenance costs, and strict requirements for environmental temperature and humidity. In laboratory use, its automation level is low, requiring specially trained technicians to operate it. Furthermore, the instrument's testing speed is relatively slow, often requiring extensive sample pretreatment before analysis, resulting in relatively low analytical efficiency.
[0003] Surface-enhanced Raman scattering (SERS) is a promising technique for detecting single molecules of Raman-active substances. When molecules adsorb onto the surfaces of noble metals such as gold and silver, their Raman scattering intensity increases by several or even tens of orders of magnitude—this is the phenomenon of surface-enhanced Raman scattering. Biosensors based on surface-enhanced Raman scattering exhibit excellent sensitivity, requiring only trace amounts of sample, and are widely used in biosensing and trace detection. High-sensitivity surface-enhanced Raman scattering substrates require hotspot regions with nanostructures, such as nano-gap, nano-tip, and nanopore, because molecules near the hotspots provide most of the surface-enhanced Raman scattering signal. Over the past few decades, based on advancements in hotspot engineering and molecular manipulation techniques, surface-enhanced Raman scattering substrates have been extensively studied, significantly improving their detection performance. However, despite their extremely high detection sensitivity, reaching the single-molecule level, surface-enhanced Raman scattering substrates have high substrate requirements, complex preparation and surface modification processes, high manufacturing costs, and low production efficiency. Therefore, surface-enhanced Raman scattering substrate technology is mainly used by top international and domestic laboratories for single-molecule scientific research and has not yet been widely applied to the practical detection of single-molecule samples.
[0004] In terms of hot spot engineering technology, including top-down methods such as photolithography and bottom-up methods such as chemical growth and self-assembly, in-depth research has been conducted. The development of these technologies has greatly promoted the improvement of surface-enhanced Raman scattering detection performance. There are two main methods for high-quality metal nanoclusters in surface-enhanced Raman scattering substrates: (1) Chemical modification method. In this method, the surface of nanoparticles is modified with biomolecules or other small molecules, and then clusters are formed through self-assembly. The steps of this method are relatively complex, and the molecules modified on the surface of nanoparticles may hinder the probe molecules from entering the "hot spot", thereby affecting the sensitivity of surface-enhanced Raman scattering detection or interfering with the Raman spectrum. (2) Template-assisted induction method. This method uses focused ion beam, electron beam lithography or block copolymers to prepare nanostructure arrays, and then the nanoparticles are self-assembled inside the array to form clusters. The advantage of this method is that the prepared clusters are uniformly distributed, but the steps are relatively complex, time-consuming, require expensive equipment, and it is difficult to prepare large-area nanoparticle clusters. In addition, the current surface-enhanced Raman scattering substrates are still made of precious metals such as gold, silver, and copper, which cannot selectively identify target molecules. Furthermore, it suffers from problems such as high cost, complex process, easy oxidation, poor spectral stability, and poor repeatability, which greatly limit the development of surface-enhanced Raman scattering technology in practical applications.
[0005] In the field of molecular manipulation technology, various methods have been developed, mainly including superhydrophobic surface-induced enrichment, directional capture of chemical analytes, and concentration using adsorbent materials, achieving ultra-high sensitivity. Superhydrophobic surface-induced enrichment uses a non-wetting matrix to enrich water molecules; however, the surface preparation process is often complex and time-consuming, and the operation of droplet evaporation depends on specific instruments and the surrounding environment, which are impractical for simpler devices. Direct capture of chemical analytes utilizes surface chemical modification to selectively capture analyte molecules, but the strict requirements on the types of molecules captured limit the applicability of this strategy. Concentration using adsorbent materials selectively adsorbs molecules using secondary adsorbents, but this strategy is currently mainly focused on proof-of-concept. Current methods for molecular manipulation require complex preparation processes or specific analytes, which still limit their application in the laboratory and also result in poor applicability in practical applications. These methods are difficult to implement in simple, practical devices.
[0006] Patent application CN112540070B discloses a test strip kit for detecting anticancer drugs in body fluids and its preparation and use method. The test strip kit includes test strips and a detection box. The tip of the test strip is deposited with metal nanomaterials as a SERS substrate to enhance the Raman scattering signal. The test strip kit includes an injector and a box body. The box body is provided with a ramp for placing the test strips and a cavity for placing the injector. The tip of the test strip is placed on the ramp, and the tail core is placed directly below the injector. It can utilize the capillary force and gravity of the test strip itself to make the tip of the paper gather more sample solution, thereby improving the pre-concentration performance and detection sensitivity. However, because the distribution of metal nanomaterials on the paper is relatively dispersed and is located on the surface of the paper without entering the gaps in the paper fibers, there are fewer hot spots, and the molecules gathered at the tip of the paper do not make sufficient contact, so it is not possible to achieve single-molecule level detection. Summary of the Invention
[0007] To overcome the problems existing in the prior art, the present invention aims to provide a single-molecule Raman detection test kit and its usage method, which combines a polymer-assisted printing method with a tip enrichment method, thereby achieving a 41-fold improvement in surface-enhanced Raman scattering detection performance for hot spots dominated by Au@Ag NPs clusters at the microscopic level. By optimizing the fluid velocity through the design of the spiral sampler and the inclined test paper slot, the directional molecular enrichment at the hot spots is promoted at the macroscopic level, achieving a 39.5-fold improvement in surface-enhanced Raman scattering detection performance. In practical sample applications, the detection limit of this test kit reaches 10... -9 M has high detection sensitivity and can achieve detection at the single-molecule level.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0009] A single-molecule Raman detection test kit includes a box body 1, a test strip groove 3 on one side of the box body 1, and a sample injection mechanism 2 on the other side; the test strip groove 3 is inclined, and a test strip 4 with a pointed end is placed in the test strip groove 3, with the tip of the test strip 4 located at the low point of the inclined surface of the test strip groove and the tail end of the test strip 4 located at the high point of the inclined surface of the test strip groove; the sample injection mechanism 2 includes a channel 5, the bottom of the channel 5 being located above the high point of the inclined surface of the test strip groove, and a spiral sampler 6 is placed in the channel 5.
[0010] The spiral sampler 6 includes a liquid storage tank 7, an inlet 8 above the liquid storage tank 7, and an outlet 9 below the liquid storage tank 7. The outlet 9 is connected to the inlet end of the spiral tube 10 below, and the outlet end of the spiral tube 10 is suspended above the highest point of the test paper tank 3.
[0011] The test paper groove 3 forms an angle of 20-40° with the horizontal plane.
[0012] The test paper trough 3 is provided with a cover plate 11; a waste liquid pool 12 is provided below the lowest point of the test paper trough 3.
[0013] The liquid inlet 8 of the liquid storage tank 7 is equipped with a dust cover 13.
[0014] The inner diameter of the spiral tube 10 is 0.4 mm to 1 mm; the length is 39 mm to 51 mm.
[0015] The test paper 4 is 10 mm to 110 mm long, and the included angle of the paper tip is 10° to 30°.
[0016] The test strip 4 is a paper substrate with Au@Ag NPs clusters deposited on the paper tip.
[0017] The Au@Ag NPs clusters deposited at the tip of the test paper 4 are obtained by mixing PEO (0.1 wt% ~ 0.5 wt%) and Au@Ag NPs aqueous solution (1.56 nM ~ 4.68 nM) at a volume ratio of 1:10 to 1:30, and then using a polymer-assisted printing method.
[0018] A method for using a single-molecule Raman detection test kit includes the following steps:
[0019] Step 1. Place the test strip 4 into the tilted test strip slot 3;
[0020] Step 2. Rinse the spiral sampler 6 with deionized water 3-5 times. After drying, place the spiral sampler 6 in the sample injection mechanism 2, with the outlet end of the spiral tube 10 suspended above the tail end of the test paper 4.
[0021] Step 3. Drop the analyte solution into the inlet of the spiral sampler 6. Driven by the component vectors of gravity and capillary force, the liquid is transported along the inclined test paper 4 to the tip of the test paper for adsorption and fills the surface and gaps of the Au@AgNPs clusters at the tip of the paper, thus completing the enhanced enrichment of the analyte molecules. Excess analyte solution flows into the waste liquid pool 12.
[0022] Step 4. After the entire test kit has been air-dried, perform the SERS measurement;
[0023] Step 5. Quantitatively analyze the measurement results using the calibration curve.
[0024] Compared with the prior art, the present invention has the following inventiveness:
[0025] 1. This invention synergizes polymer-assisted printing-derived Au@Ag NPs clusters at the test strip tip with an enhanced tip enrichment method used in the test strip cartridge. The test strip tip is made by adding water-soluble long-chain polymer polyethylene oxide (PEO) to an Au@Ag NPs aqueous solution, inducing local aggregation by entanglement of adjacent nanoparticles. The dispersion of the aggregated nanoparticles can reach 1.77. The surface-enhanced Raman scattering (SERS) detection results match the theoretical enhancement simulated over a large area. Microscopically, the hotspots dominated by Au@Ag NPs clusters achieve a 41-fold improvement in SERS detection performance. Macroscopically, directional molecular enrichment at the hotspots is achieved through simulation and optimization of fluid velocity, resulting in a 39.5-fold improvement in SERS detection performance. In the application of model molecules, the detection limit of this test strip cartridge can reach 10. -12 M; In practical sample applications, the detection limit of this test kit reaches 10. -9 M has high detection sensitivity, reaching the level of single-molecule detection.
[0026] 2. This invention utilizes the inclined arrangement of the test strip groove 3 in the test strip cartridge and the spiral sampler 6. Driven by the components of gravity and capillary force, the analyte solution is transported along the inclined test strip 4 to the tip of the test strip for adsorption, thereby filling the surface and gaps of Au@Ag NPs clusters and achieving enhanced enrichment of analyte molecules. During this process, changes in the diameter and length of the spiral channel can alter the fluid resistance and the fluid velocity at the outlet, thus affecting the residence time of the solution enriched on the paper tip. The slope of the paper tip can change the flow rate of the analyte solution, further affecting the retention time, while the length of the paper tip directly changes the solution retention time. Since sufficient retention time is a prerequisite for molecular enrichment and adsorption on plasma clusters, the parameters provided in this invention are crucial to the detection performance of the test strip cartridge, enabling optimal molecular enrichment and localization on small clusters, which helps to reduce the detection limit.
[0027] 3. The test strip box of this invention has a simple structure, is easy to operate, and has good stability and repeatability. The RSD during the experiment is 8.26%, and the correlation coefficient between the measured concentration and the actual concentration can reach 0.98. It can accurately perform quantitative analysis of molecules, with high detection efficiency and low cost.
[0028] In summary, this invention combines polymer-assisted printing to obtain Au@Ag NPs clusters at the test strip tip with an enhanced tip enrichment method used in the test strip cartridge for practical applications requiring high sensitivity, achieving a sensitivity of 10 in actual sample applications. -9 The detection limit of M enables detection at the single-molecule level, with high detection sensitivity, ease of operation, and higher efficiency. Attached Figure Description
[0029] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the embodiments of the present invention will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 This invention relates to a single-molecule Raman detection test kit, wherein... Figure 1 (a) is a structural assembly diagram. Figure 1 (b) is a structural decomposition diagram.
[0031] Figure 2 This is a schematic diagram of the spiral sampler of the present invention, wherein, Figure 2 (a) is a schematic diagram of the fluid flow. Figure 2 (b) is a schematic diagram of the structure.
[0032] Figure 3 This is a schematic diagram of the detection principle of the present invention.
[0033] Figure 4 This describes the formation process of Au@Ag NPs clusters deposited at the tip of the test strip.
[0034] Figure 5 Characterization of polymer-assisted printing processes; among which, Figure 5 (A) is a TEM image of Au@AgNPs without PEO (polyethylene oxide), with a scale bar of 200 nm; Figure 5 (B) is a TEM image of Au@Ag NPs containing PEO, with a scale bar of 100 nm; Figure 5 (C) shows the UV-Vis spectra of Au@Ag NPs containing PEO and those without PEO, as well as the PEO solution; Figure 5 (D) Surface-enhanced Raman scattering spectra of Au@Ag NPs with different PEO contents (wt%) at 1175 cm⁻¹ -1 The peak area and the corresponding degree of dispersion at the specified location; Figure 5 (E) is an optical micrograph of Au@Ag NPs printed samples with different PEO contents. The scale bar is 500 μm.
[0035] Figure 6 For large-area simulation of the statistical distribution of nanoclusters; among which, Figure 6 (A) Images i-iii are SEM images of Au@Ag NPs at concentrations of 1.56 nM, 2.34 nM and 4.68 nM, respectively, with a scale bar of 500 nm. Figure 6(B) i-iii are large-area simulation models of Au@Ag NPs with concentrations of 1.56 nM, 2.34 nM and 4.68 nM, respectively; Figure 6 (C) In the middle i-iii, the electric field distributions on the xy plane obtained by FDTD simulation of Au@Ag NPs with concentrations of 1.56 nM, 2.34 nM and 4.68 nM respectively. Figure 6 In (D), i-iii represent the amplified distribution of the local electric field of the PEO solution, the amplified distribution of the local electric field of Au@AgNPs containing PEO, and the amplified distribution of the local electric field of Au@AgNPs without PEO, respectively. Figure 6 (E) Printed substrates with different concentrations of Au@Ag NPs were used in the detection of CV at 1175 cm⁻¹. -1 The peak area and corresponding average of the SERS spectrum / 0| 4 .
[0036] Figure 7 This is the paper tip enrichment process of the present invention; wherein, Figure 7 (A) is a schematic diagram of the inside of the test strip box, showing the enrichment process of the paper tip; Figure 7 (B) is an optical micrograph and a fluorescence image of the paper tip printed with Au@Ag NPs (scale bar 500 μm), showing that the enriched fluorescent molecules are localized on the Au@Ag NPs clusters; Figure 7 (C) shows a 3D view and actual photograph of the spiral sampler; Figure 7 (D) shows the velocity distribution from the COMSOL simulation; Figure 7 (E) Screw injectors with different channel diameters at 1175 cm -1 The surface-enhanced Raman scattering spectrum characteristic peak area and fluid resistance at the CV; Figure 7 (F) shows a schematic diagram and actual photograph of the 3D printed test kit; Figure 7 (G) Different spiral injector inclinations at 1175 cm -1 The area of the characteristic peaks in the surface-enhanced Raman scattering spectrum at CV; Figure 7 (H) is a schematic diagram and actual photograph of the paper tip; Figure 7 (I) For paper tips of different lengths at 1175 cm -1 The area of the characteristic peaks in the surface-enhanced Raman scattering spectrum at CV; Figure 7 (J) represents the normalized molecular concentration and (K) represents the fluid velocity distribution; Figure 7 (L) represents the normalized molecular concentration of COMSOL at the solid-liquid interface at NPs and other locations.
[0037] Figure 8A comparison of polymerization and flow methods; among which, Figure 8 (A) SEM images (scale bar is 500 nm) of three aggregation methods, namely i. drop addition, ii. printing and iii. PEO printing. Figure 8 (B) Schematic diagrams of three flow methods, namely i. non-directional flow, ii. directional flow, and iii. enhanced directional flow; Figure 8 (C) SERS spectra of CVs produced by different aggregation methods at 1175 cm⁻¹ -1 The peak area; Figure 8 (D) SERS spectra of CVs produced by different flow methods at 1175 cm⁻¹ -1 The peak area.
[0038] Figure 9 The results are obtained by single-molecule Raman detection via micro-macro SERS; among which, Figure 9 (A) For concentrations from 10 -7 Up to 10 -11 SERS spectrum of M's CV; Figure 9 (B) is the corresponding SERS spectrum at 1175 cm⁻¹ -1 The peak area; Figure 9 (C) is 1175cm -1 The linear relationship between peak area and logarithmic concentration of CV; Figure 9 (D) To collect 10 units of 10 from a single operation -6 The M CV spectrum demonstrates the stability of the single-molecule device; Figure 9 (E) is 1175 cm, corresponding to stability. -1 The peak area of the CV at that location; Figure 9 (F) For each operation at 1175 cm -1 The average peak area at the point is used to demonstrate the reproducibility of the single-molecule device.
[0039] Figure 10 Application of single-molecule Raman detection test strips in the detection of contaminants and photosensitizers; Figure 10 (A) represents a concentration from 10 -6 Up to 10 -10 Surface-enhanced Raman scattering spectrum of M-methylene blue (MB); Figure 10 (B) represents a concentration from 10 -6 Up to 10 -10 The surface-enhanced Raman scattering spectrum of M-methylene blue (MB) at 1150 cm⁻¹ -1 and 1250 cm -1 Peak area between; Figure 10 (C) shows the linear relationship between peak area and the logarithmic concentration of methylene blue; Figure 10(D) is the detection of real river water samples on a single-molecule paper box; Figure 10 (E) represents a concentration of 10. -6 Up to 10 -10 Surface-enhanced Raman scattering spectrum of malachite green (MG) of M; Figure 10 (F) represents a concentration of 10. -6 Up to 10 -10 The surface-enhanced Raman scattering spectrum of malachite green (MG) at 650 cm⁻¹ -1 The peak area; Figure 10 (G) represents the linear relationship between peak area and logarithmic concentration of malachite green.
[0040] In the diagram: 1. Box body; 2. Sample injection mechanism; 3. Test paper trough; 4. Test paper; 5. Channel; 6. Screw injector; 7. Liquid storage tank; 8. Liquid inlet; 9. Liquid outlet; 10. Solenoid; 11. Cover plate; 12. Waste liquid pool; 13. Dust cover. Detailed Implementation
[0041] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0042] The present invention will now be described in detail with reference to the accompanying drawings.
[0043] like Figures 1-3 As shown, in order to achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0044] A single-molecule Raman detection test kit includes a box body 1, a test strip groove 3 on one side of the box body 1, and a sample injection mechanism 2 on the other side; the test strip groove 3 forms an angle of 20-40° with the horizontal plane, and a test strip 4 with a pointed end is placed in the test strip groove 3, with the tip of the test strip 4 placed at the lowest point of the test strip groove 3 and the tail end of the test strip 4 placed at the highest point of the test strip groove; the sample injection mechanism 2 includes a channel 5, the bottom of the channel 5 being located above the highest point of the test strip groove 3, and a spiral sampler 6 is placed in the channel 5.
[0045] The spiral sampler 6 includes a liquid storage tank 7, an inlet 8 above the liquid storage tank 7, and an outlet 9 below the liquid storage tank 7. The outlet 9 is connected to the inlet end of the spiral tube 10 below, and the outlet end of the spiral tube 10 is suspended above the highest point of the test paper tank 3.
[0046] The test paper trough 3 is provided with a cover plate 11; a waste liquid pool 12 is provided below the lowest point of the test paper trough 3.
[0047] The liquid inlet 8 of the liquid storage tank 7 is equipped with a dust cover 13.
[0048] The inner diameter of the spiral tube 10 is 0.5 mm; the length is 51 mm.
[0049] The test paper 4 is 50 mm long and has a 10° angle between its tip and the tip.
[0050] The test strip 4 is a paper substrate with Au@Ag NPs clusters deposited on the paper tip.
[0051] The Au@Ag NPs clusters deposited at the tip of the test paper 4 were obtained by mixing PEO (0.1 wt% ~ 0.5 wt%) and Au@Ag NPs aqueous solution (1.56 nM ~ 4.68 nM) at a volume ratio of 1:25, and then using the printing apparatus and method described in CN110142962A, "A printing apparatus and method for capillary-driven paper-based nanomaterials", that is, by a polymer-assisted printing method.
[0052] A method for using a single-molecule Raman detection test kit includes the following steps:
[0053] Step 1. Place the test strip 4 into the tilted test strip slot 3;
[0054] Step 2. Rinse the spiral sampler 6 with deionized water 3-5 times. After drying, place the spiral sampler 6 in the sample injection mechanism 2, with the outlet end of the spiral tube 10 suspended above the tail end of the test paper 4.
[0055] Step 3. Drop the analyte solution into the inlet of the spiral sampler 6. Driven by the component vectors of gravity and capillary force, the liquid is transported along the inclined test paper 4 to the tip of the test paper for adsorption and fills the surface and gaps of the Au@AgNPs clusters at the tip of the paper, thus completing the enhanced enrichment of the analyte molecules. Excess analyte solution flows into the waste liquid pool 12.
[0056] Step 4. After the entire test strip box has been ventilated and dried, SERS measurements are performed using a portable Raman spectrometer;
[0057] Step 5. Quantitatively analyze the measurement results using the calibration curve.
[0058] The working principle of this invention is as follows:
[0059] After assembling the test strip box, the test strip 4 with Au@Ag NPs clusters deposited on its tip is placed in the test strip trough 3. The analyte solution is dripped into the injection mechanism 2. The analyte drips through the injection mechanism 2 onto the tail end of the test strip 4. Driven by the components of gravity and capillary force, it is transported along the inclined test strip 4 to the tip of the test strip 4 for adsorption, thereby filling the surface and gaps of the Au@Ag NPs clusters and completing the enhanced enrichment of analyte molecules. Excess analyte solution flows into the waste liquid pool 12. After the entire test strip box is ventilated and dried, SERS measurement is performed. The measurement results are then quantitatively analyzed using a calibration curve.
[0060] In this process, the tip of test paper 4 is made by adding water-soluble long-chain polymer polyethylene oxide (PEO) to an aqueous solution of Au@Ag NPs. This induces local aggregation by entanglement of adjacent nanoparticles. The Au@Ag NPs aggregated by PEO are then further concentrated by a capillary force-driven printing method (polymer-assisted printing method) to obtain small clusters of Au@Ag NPs. PEO slows down the deposition rate of Au@Ag NPs, causing them to assemble a large number of small clusters during the printing process, thereby inducing the formation of large-area hot spots and providing SERS performance with strong stability and high sensitivity.
[0061] By tilting the test strip slot 3 in the test strip cartridge and using the spiral injector 6, the analyte solution is transported along the tilted test strip 4 to the tip of the test strip 4 under the drive of gravity and capillary force components. This allows for adsorption, filling the surface and gaps of the Au@Ag NPs clusters and achieving enhanced enrichment of the analyte molecules. During this process, changes in the diameter and length of the spiral channel alter the fluid resistance and outlet velocity, thus affecting the residence time of the solution on the paper tip. The slope of the paper tip changes the flow rate of the analyte solution, further influencing the retention time, while the length of the paper tip directly changes the retention time. Since sufficient retention time is a prerequisite for molecular enrichment and adsorption on plasma clusters, the parameters provided in this invention are crucial for the detection performance of the test strip cartridge, enabling optimal molecular enrichment and localization on small clusters, thus helping to lower the detection limit.
[0062] To demonstrate the role of polymer deposition in the formation of plasma clusters, the polymer deposition process was characterized.
[0063] The gold nucleus (gold seed) of Au@Ag NPs exhibits a UV-Vis absorption peak at 520 nm, with a size of approximately 20 nm. The statistical value of the prepared Au@Ag NPs in the TEM image is 49 ± 7 nm. Figure 5Image A shows the typical linear distribution of the nanoparticles. The corresponding magnified image reveals the narrow gaps between the Au@Ag NPs. These results indicate that the Au@Ag NPs exhibit good monodispersity in the absence of PEO. UV-Vis spectroscopy shows... Figure 3 The absorption peak of Au@Ag NPs in C is at 428 nm, with an absorbance of 0.334 au. However, after the addition of PEO, Figure 5 The TEM image and corresponding magnified image in B show that PEO forms clusters around Au@Ag NPs aggregated together. The absorption peak and absorbance change to 419 nm and 0.354 au, respectively. Figure 5 C). This indicates a decrease in the number of NPs in the solution. The above results suggest that PEO promotes the local aggregation of Au@Ag NPs. Au@Ag NPs solutions containing PEO were printed as circular patterns on filter paper. Optical micrographs of the printed patterns show that the area of the black pixels (i.e., Au@Ag NP clusters) decreases as the PEO content increases from 0.1% to 0.5%. Figure 5 E). Dispersion is defined as the distribution of Au@Ag NPs within the circular pattern created by deposition; dispersion is calculated using the following formula:
[0064] (1)
[0065] Where BC (black_count) is the number of black pixels (i.e., Au@Ag NPs within the filter paper), AP (area_pixel) is the area of a single pixel, and r is the channel radius of the printed chip used.
[0066] The dispersion first decreases at 2.13, then fluctuates around 1.2. Figure 5 D. This indicates that the clusters become more concentrated, possibly due to the increased viscosity after the addition of PEO, which restricts capillary flow in the filter paper. And the crystal violet CV at 1175 cm⁻¹... -1 The corresponding SERS peak area first increases and then decreases. Figure 5 D, and reached its maximum at a PEO content of 0.3%, with a dispersion of 1.77, which is the optimal PEO content. This result implies that appropriately concentrated NPs are beneficial for Raman scattering, while excessive concentration may lead to a reduction in the Raman signal. Therefore, polymer-induced local aggregation and printing to produce large-area concentrations were used to select the optimal PEO content based on dispersion and peak area of SERS characteristic peaks.
[0067] Large-area simulations were performed using the Finite-Difference Time-Domain (FDTD) method. FDTD can simultaneously calculate multiple frequency ranges in a single simulation run and naturally handles various linear material properties, thus correlating theoretical enhancement with SERS testing. Paper-tip SERS substrates were fabricated and characterized using Au@AgNPs at concentrations of 1.56 nM, 2.34 nM, and 4.68 nM via polymer-assisted printing. SEM images at concentrations of 1.56 nM, 2.34 nM, and 4.68 nM are shown in [images]. Figure 6 A(i-iii) and Figure 6 B(i-iii) counted and analyzed the number and type of Au@Ag NPs clusters. The average number of NPs in the images of the three concentrations were 547, 634, and 1596, respectively, in a ratio of 17:20:50. The Au@Ag NPs clusters were classified into three types: single (1 particle), small clusters (2-10 particles), and large clusters (>10 particles). The average percentage of single particles was similar in the four SEM images for each concentration. The average percentage of small clusters at 2.34 nM was 58.6%, far exceeding the other two concentrations, while the content of large clusters at this concentration was only 20.2% among the three concentrations. The content of large clusters was highest at the 4.68 nM concentration. The paper tip SERS substrate was modeled as a cellulose cube with Au@Ag NPs, and 170, 200, and 500 particles were used in the simulation models for the three concentrations, respectively. Figure 6 B), through formula
[0068]
[0069] Where C is the number of nanoparticles, r is the radius of the silver shell, and L and W are the length and width of the cellulose cube with Au@Ag NPs, respectively, with coverage rates of 15.4%, 18.1%, and 45.3%. Therefore, based on the statistical results of SEM images, three large-area simulation models were established.
[0070] Figure 6 C(i-iii) shows the simulated electric field distribution in the xy plane for the three concentrations, revealing three large-area electric fields and distinct hotspots around or between clusters of NPs. The distribution of hotspots is shown from... Figure 6 C(i) becomes denser from (iii), Figure 6 C(ii) provides a relatively uniform distribution. Furthermore, in Figure 6 Of the three electric field distributions in C(ii), the strongest hotspot occurs at 2.34 nM, with an electric field strength of 178, which is significantly higher than the 109 and 126 in the other two distributions (through...). Figure 6 In C, color is used to determine the electric field strength (different colors represent different electric field intensities). Figure 6 D(i-iii) shows typical local electric field distributions for the three types of clusters, which are magnified images of the three electric field distributions, respectively. Meanwhile, the average || is calculated using the overall electric field strength. / 0| 4 (Theoretical enhancement factor) shows a trend of first increasing and then decreasing from 1.56 nM to 4.68 nM, reaching a maximum at 2.34 nM. / 0| 4 Also with average | / 0| 4 A similar trend was observed. SERS tests showed that the peak area of the SERS spectrum first increased and then decreased with increasing concentration from 1.56 nM to 4.68 nM, reaching a maximum at a concentration of 2.34 nM, which was selected as the optimal concentration for Au@Ag NPs. This result is consistent with the trend predicted by theoretical simulations. Figure 6 (E). This phenomenon is closely related to the coverage and distribution of Au@Ag NPs clusters. At low concentrations, the coverage is low and the cluster distribution is sparse, while at high concentrations, the coverage is large, leading to hotspot shading, especially from a large number of large clusters. This results in a decrease in the total electric field and SERS intensity. However, in this work, at a suitable concentration, such as 2.34 nM, small clusters dominate, with a small coverage area, inducing a strong total electric field without shading. Therefore, through large-area simulations, the SERS results match the theoretical enhancement, and hotspots dominated by small clusters are more easily generated over large areas, playing a key role in polymer-assisted printing. This method provides SERS performance with strong stability and high sensitivity.
[0071] By enhancing directional enrichment at the tip, optimal molecular enrichment and local properties can be obtained. Figure 7 Paper tips are assembled onto the bevels of a 3D-printed kit to modulate enrichment performance. A schematic diagram of the kit illustrates the detailed process of the tip enrichment method. Figure 7In step A), the analyte solution is added to the inlet of a spiral injector and flows through a spiral channel and outlet. The solution is then dropped onto the tail of a paper tip, where it is accelerated along an incline towards the tip by the combined forces of gravity and capillary forces. Simultaneously, the analyte is transported to the tip for adsorption, further filling the surface and interstices of Au@Ag NPs clusters. The flow process is completed within 5 minutes, and the SERS signal is detected using a portable Raman spectrometer after 15 minutes of drying. Changing the diameter and length of the spiral channel alters the fluid resistance and outlet velocity, thus affecting the residence time of the enriched solution on the paper tip. The slope of the paper tip changes the flow rate of the analyte solution, further influencing the retention time, while the length of the paper tip directly alters the solution retention time. Since sufficient retention time is a prerequisite for molecular enrichment and adsorption on plasma clusters, these parameters are crucial to the detection performance of the test strip. Figure 7 The left side of B shows that small clusters exist only at the tip of the paper, and the fluorescein molecule indicates that the molecular enrichment site is concentrated at the tip. Figure 7 (B on the right) indicates the initial localization of the enriched luciferin molecules on the cluster.
[0072] COMSOL was used to design and simulate helical injectors of different diameters to explore the relationship between fluid velocity and SERS enhancement. Figure 7 C-7D). Figure 7 D shows that, theoretically, the flow velocity at the outlet increases as the solenoid diameter of the helical samplers 2-4 increases from 0.4 mm to 1 mm. The fluid resistance formula for the helical sampler is... The simulation results are given, where ΔP is the pressure drop through the channel [Pa] and Q is the volumetric flow rate [m]. 3 ·s -1 The calculated fluid resistance decreases rapidly. Figure 7 E), especially at a diameter of 0.4 mm, the resistance is too great to flow out of the outlet, and the SERS spectrum of CV is at 1175 cm⁻¹. -1 The corresponding peak area at that point is considered to be 0. As the diameter of the solenoid tube increases from 0.5 mm to 1 mm (taking values of 0.4, 0.5, 0.6, 0.75, and 1.0 mm respectively), the peak area decreases from 102873 to 15702. Figure 7(E) It was determined that 0.5 mm was the optimal diameter. This reduction is likely due to the higher flow rate, causing the solution to flow rapidly over the tip filled with plasma clusters, resulting in almost no residence time for absorption at the paper tip, leading to tip enrichment and suboptimal adsorption near the clusters. Simulations and tests were conducted on spiral samplers of different lengths, showing that as the length increased from 39 mm to 51 mm, the fluid velocity decreased slightly, while the fluid resistance increased accordingly, allowing for more retention time and better localization. This contributed to a slight increase in the corresponding peak area.
[0073] The flow rate of the analyte solution on the tilted paper tip is adjusted by the slope of the test strip cartridge to achieve optimal enrichment and localization. Figure 7 F shows the design and actual photograph of the 3D-printed test kit, illustrating the kit's slope. As the slope of the test kit increases from 20° to 40°, the peak area initially increases significantly, and then... Figure 7 The concentration of F decreases, with the largest peak area reached at 30°. This can be attributed to the appropriate component vector of gravity FG at 30°, which is used for enrichment and localization around small clusters. For small-angle test kit slopes, the component vector is too small, and capillary force FC cannot drive enough solution to reach the tip within 5 minutes, resulting in a small number of molecules localizing on small clusters. For larger angles, the component vector increases because directional flow is an accelerating motion; this increase leads to a greater increase in flow velocity near the tip, causing the solution to rapidly flow away from the tip, resulting in short retention time and poor enrichment. This trend is supported by previous work on test kits. Figure 7 H shows the design and actual photograph of the paper tip, indicating its length. As the paper tip length increases from 10 mm to 110 mm, the peak area first increases rapidly and then continues to decrease. Figure 7 The flow rate (I) reaches its maximum at 50 mm. For lengths less than 50 mm, the flow distance is small and the retention time is short. For lengths greater than 50 mm, the height of the test strip box is increased to maintain a constant box slope. Similar to the case at large angles, this also leads to increased flow rate at the tip, resulting in poor molecular enrichment and localization on plasma clusters. The corresponding peak areas of test strip boxes at different angles decrease rapidly as the angle increases from 10° to 30°, with the largest peak area reached at 10°. This phenomenon can be explained by shape-enhanced capillary effects, consistent with previous work on paper tips. These results indicate that the test strip box improves the localization of enriched molecules on Au@Ag NPs clusters. This is likely due to the spatial proximity of the enriched molecules to Au@Ag NPs, filled by the capillary network of the cellulose tip, which facilitates molecular absorption at the solid-liquid interface of the NPs. Therefore, through system optimization, the enrichment and localization of molecules on plasma clusters are improved.
[0074] Furthermore, the absorption of NPs by molecules was simulated using COMSOL. The spatial positions of molecules and NPs within the capillary channel were also considered in the simulation model. Figure 7 J shows that the molecular transfer rate at the surface and interstitial spaces of NPs is lower than at other sites, which ensures that the molecules have sufficient residence time at the interface for absorption, which is beneficial for molecular localization. The surface and interstitial spaces can effectively trap molecules, which is consistent with experimental results. Figure 7 (K-7L). Therefore, a 30° slant of the paper box, a 50 mm paper tip length, and a 10° angle can achieve optimal molecular enrichment and localization on small clusters, which helps to reduce the detection limit.
[0075] 4.4 Comparison with other polymerization and flow methods
[0076] Interpretability is crucial for realizing widely applicable SERS detection strategies. Here, a polymer-assisted printing process and a tip enrichment process are combined in a micro-macro dual SERS detection strategy. These two processes are compared with other aggregation and flow methods to further explain the proposed strategy and demonstrate its advantages. Figure 8 Other aggregation methods include dropwise addition, dropwise addition with PEO, and polymer-assisted printing; other flow methods include non-directional flow and directional enrichment.
[0077] Polymer-assisted printing methods were compared with other polymerization methods to explain the relationship between PEO and printing. In the dropwise addition method, Au@Ag NPs are directly added to the filter paper; in the PEO-containing dropwise addition method, Au@Ag NPs containing PEO are directly added to the filter paper; and in the printing method, Au@Ag NPs without PEO are printed onto the filter paper. Schematic diagrams and SEM images of the polymerization methods illustrate the polymerization process and actual results. Figure 8 A(i-iii)). The drop plot illustrates monodisperse Au@Ag NPs ( Figure 8 A(i)), while the corresponding SEM images showed fewer individual Au@Ag NPs. Dropping plots with PEO illustrate similar dropping results. Printing plots illustrate concentrated Au@Ag NPs ( Figure 8 A(ii)), and Figure 8 A(ii) shows more NPs. After adding PEO printing, Figure 8 A(iii) shows numerous small clusters of Au@Ag NPs. Optical micrographs under previously optimal conditions show a large number of black pixels (i.e., clusters of NPs) with better dispersion and almost no blank areas. These phenomena imply the formation of numerous relatively concentrated hotspots over a large area. The SERS peak areas printed with PEO are 41 times, 12 times, and 10 times larger than those of the above three, respectively. Figure 8 C). This indicates that the polymer and printing produce a synergistic effect in the polymer-assisted printing process, providing significant SERS enhancement through abundant small clusters.
[0078] The tip enrichment process was also compared with other flow methods to explain the role of orientation and the 3D-printed test kit. Schematic diagrams of the three flow methods illustrate their flow processes. Figure 8 B(i-iii)). In non-directional flow, the analytical solution is dropped onto one side of a circular paper substrate, and detection is performed on the other side. Figure 8 B(i)), while in directional enrichment, the analytical solution is dropped onto the tail of a flat paper tip, and detection is performed at the tip ( Figure 8 B(ii)). In non-directional flow, the solution flows randomly within the paper substrate, with a small amount of solution reaching the circular areas of the printed Au@Ag NPs, providing almost no enrichment effect. However, in directional enrichment and enhanced directional enrichment (i.e., tip enrichment process), the solution flows along the length of the paper tip towards the black areas (i.e., Au@Ag NP clusters), producing a good tip enrichment effect. The difference between existing directional enrichment methods and the enhanced directional enrichment of this invention lies in the introduction of a 3D-printed test paper cartridge in the enhanced directional enrichment to achieve a suitable flow rate ( Figure 8 B(iii)). The peak area of the enhanced directional enrichment increased by 39.5 times and 10.3 times compared to the two methods mentioned above, respectively. Figure 8 (D) demonstrates that the tip enrichment process is an enhanced directional enrichment, producing a significant SERS enhancement effect. Therefore, testing the improved test kit demonstrates the significant advantages of this detection strategy in terms of reliable hot spots and enhanced enrichment, as well as its great potential in single-molecule detection.
[0079] The SERS performance of a single-molecule Raman detection test kit designed using a micro-macro dual SERS detection strategy was tested, including detection limit, quantitation analysis, enhancement factor (EF), stability, and repeatability, to verify the improved detection capability of the test kit. Figure 9 ). Figure 9 A shows the SERS spectra of CV at different concentrations, at 10 -7 At M, 1175 cm -1 There is a strong in-plane bending mode of CH in the vicinity, and it decreases with concentration, especially at 10. -12 This is also visible at time M. The peak area of this Raman shift is plotted against 10... -9 M to 5×10 -12 The M concentration change curve and the calibration curve can be successfully fitted. R 2 0.95 ( Figure 9 C). Through the formula and The calculated limits of detection (LOD) and quantitation (LOQ) are 0.33 × 10⁻⁶. -12 M and 5.56×10 -12 M indicates an extremely low detection limit. This is determined by the formula... , where I SERS and I bare These are the peak areas on the paper test kit and the silicon wafer, respectively, while c SERS and c bare The concentration absorbed on the above-mentioned matrix is used to calculate the AEF as 0.36 × 10⁻⁶. 10 The stability of the test kit was explored by randomly collecting 10 spectra during a single operation. Figure 9 D shows 10 similar spectra. Figure 9 E provides an approximate peak area with an average of 128,868 and an RSD of 7.04%. Repeatability was explored by calculating the average of 10 spectra collected after 10 runs of the test kit. Figure 9 F shows the average spectrum and peak area for each operation, with an average value of 104557 and an RSD of 8.26%, indicating that the spectrum and peak area are close. These results demonstrate that the test kit exhibits good stability and repeatability, implying significant applicability in practical applications. Therefore, the test kit is simple to operate, possesses high sensitivity and reliable detection capability, and represents a promising high-sensitivity detection tool for practical applications.
[0080] This invention relates to a single-molecule Raman detection test kit for detecting molecules widely used in environmental monitoring and photodynamic therapy for tumors. Real samples are used to test its practical application capabilities. For example, malachite green (MG), not only a dye molecule but also a fish bactericide and insecticide, is a common water pollutant and has been banned for use in aquaculture. Methylene blue (MB), a dye and carcinogen, is used as a photosensitizer in photodynamic therapy for cancer. River water contaminated with different concentrations of methylene blue was used as real samples; these samples were collected from the Xiaohe River in Xi'an City.
[0081] Detected concentration 10 -6 M to 10 -10 An aqueous solution of M was used to verify the SERS performance of the single-molecule test strip in practical analyte applications. The SERS spectrum of MG was obtained, where the 1200 cm⁻¹ represents the curvature in the CH plane. -1 The characteristic peaks nearby decrease, at 10 -10 Visible at time M. The corresponding peak area is calculated, showing a decreasing trend. This is achieved by plotting the peak area of this Raman shift against 5 × 10⁻⁶. -8 M to 5×10 -10 A function of M concentration, quantitative curve fitting R 2 It is 0.98. (Using the formula...) and The calculated limit of detection (LOD) and limit of quantitation (LOQ) are 4.54 × 10⁻⁶. -10 M and 7.56×10 -10 M. Meanwhile, the detection concentration was 10. -6 M to 10 -10 An aqueous solution of MB was used to verify its actual detection capability. SERS spectra of MB at different concentrations are shown below. Figure 10 As shown in Figure A, the in-plane bending of the CC ring mode of MB is at 10 -6 The effect is very obvious at M, and gradually decreases as the concentration decreases, at 10 -10 This is visible at time M. The corresponding peak area shows a decreasing trend ( Figure 10 B). By plotting the peak area of this Raman shift with 5 × 10⁻⁶... -8 M to 5×10 -10 A function of M concentration can be fitted to R. 2 The calibration curve is 0.98. Figure 10 C). LOD and LOQ are 4.54 × 10⁻⁶ respectively. -10 M and 7.56×10 - 10 M. Therefore, the high sensitivity of the single-molecule test strip in aqueous solution is demonstrated by common analytes in both application areas.
[0082] In addition, the concentration in the river water is 10 -6 M to 10 -10 MG was used for validation testing. Following the standardized procedure of the single-molecule test strip, sample pretreatment and quantification were completed within 30 minutes. SERS spectra of different concentrations of MG are shown below. Figure 10 As shown in Figure D, the spectral shape and main characteristic peaks are consistent with those of the pure substance in aqueous solution, indicating that interference from impurities in real river water has been effectively eliminated. And at 1200 cm⁻¹... -1 The characteristic peaks in the vicinity decrease with decreasing concentration, at 10 -10 It is still visible at time M. The corresponding peak area shows a decreasing trend ( Figure 10 E). By plotting the peak area of this Raman shift with 5 × 10⁻⁶... -8 M to 5×10 -10 A function of M concentration can be fitted to R. 2 The calibration curve is 0.98. Figure 10 F). LOD and LOQ are 4.54 × 10⁻⁶ respectively. -10 M and 7.56×10 -10M. These results demonstrate a low detection limit and strong SERS enhancement when detecting contaminants, photosensitizers, and real samples, and show the good practicality of the single-molecule test strip, with great potential for analyte detection in more practical applications.
[0083] Traditional methods for detecting micropollutants in the environment employ chromatography as the separation process, followed by mass spectrometry, such as liquid chromatography-mass spectrometry (LC-MS). While these methods offer high sensitivity (down to the ng / L level), the instruments involved are complex and require extensive professional training for operation and maintenance. Furthermore, extensive sample pretreatment is often necessary before analysis. This translates to high cost (approximately 1000 RMB per sample) and long processing time (4 hours per sample) in practical applications. In this work, a single-molecule test kit utilizes a spiral injector and the kit's slope to control the flow rate, separating impurities and small molecules from the cellulose paper tip. This pretreatment of real pollutant samples allows for the detection of Raman signals at the paper tip, which is filled with plasma clusters. Analyte molecules are precisely enriched at the hotspot dominated by small clusters, achieving a concentration of 10-1 in practical sample applications. -9 The detection limit of M is achieved. Meanwhile, the single-molecule test strip costs only 10 yuan, a 100-fold reduction in cost, and the standardized procedure takes only 30 minutes, an 8-fold reduction in time. This not only achieves single-molecule sensitivity but also significantly reduces the cost and time of environmental monitoring.
[0084] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the scope of the technology disclosed in the present invention, and within the spirit and principles of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A single-molecule Raman detection test kit, comprising a box body (1), a test strip slot (3) provided on one side of the box body (1), and a sample injection mechanism (2) provided on the other side; characterized in that, The test strip groove (3) is inclined, and a test strip (4) with a pointed end is placed in the test strip groove (3). The tip of the test strip (4) is placed at the low point of the inclined surface of the test strip groove, and the tail end of the test strip (4) is placed at the high point of the inclined surface of the test strip groove. The sample injection mechanism (2) includes a channel (5). The bottom of the channel (5) is located above the high point of the inclined surface of the test strip groove, and a spiral sampler (6) is placed in the channel (5). The test paper (4) is a paper substrate with Au@Ag NPs clusters deposited at the paper tip; The Au@Ag NPs clusters deposited at the tip of the test paper (4) are obtained by mixing 0.1 wt% ~ 0.5 wt% polyethylene oxide and 1.56 nM ~ 4.68 nM Au@Ag NPs aqueous solution at a volume ratio of 1:10-1:30, and then printing by polymer-assisted method.
2. The single-molecule Raman detection test kit according to claim 1, characterized in that, The spiral sampler (6) includes a liquid storage tank (7), an inlet (8) is provided above the liquid storage tank (7), and an outlet (9) is provided below the liquid storage tank (7). The outlet (9) is connected to the inlet end of the spiral tube (10) below, and the outlet end of the spiral tube (10) is suspended above the high point of the test paper tank (3).
3. The single-molecule Raman detection test kit according to claim 1, characterized in that, The test paper groove (3) forms an angle of 20-40° with the horizontal plane.
4. The single-molecule Raman detection test kit according to claim 1, characterized in that, A cover plate (11) is provided on the test paper trough (3); a waste liquid pool (12) is provided below the lowest point of the test paper trough (3).
5. A single-molecule Raman detection test kit according to claim 2, characterized in that, The liquid inlet (8) of the liquid storage tank (7) is provided with a dust cover (13).
6. A single-molecule Raman detection test kit according to claim 2, characterized in that, The inner diameter of the spiral tube (10) is 0.4 mm to 1 mm; the length is 39 mm to 51 mm.
7. The single-molecule Raman detection test kit according to claim 1, characterized in that, The test paper (4) is 10 mm - 110 mm long and the included angle of the paper tip is 10° - 30°.
8. A method of using the single-molecule Raman detection test kit according to any one of claims 1-7, characterized in that, Specifically, the following steps are included: Step 1. Place the test strip (4) into the inclined test strip slot (3); Step 2. Rinse the screw injector (6) with deionized water 3-5 times. After it dries, place the screw injector (6) inside the injection mechanism (2) and suspend the screw injector (6) above the end of the test paper (4). Step 3. Drop the analyte solution into the inlet of the spiral sampler (6). Driven by the component vectors of gravity and capillary force, the liquid is transported along the inclined test paper (4) to the tip of the test paper for adsorption and fills the surface and gaps of the Au@AgNPs clusters at the tip of the paper, thus completing the enhanced enrichment of the analyte molecules. Excess analyte solution flows out. Step 4. Allow the entire test kit to air dry for 15-20 minutes before performing SERS measurements; Step 5. Quantitatively analyze the measurement results using the calibration curve.
Citation Information
Patent Citations
Paper-base nano-material printing device and method driven by capillary force
CN110142962A
Test kit for detecting anticancer drugs in body fluids, and its preparation and usage method
CN112540070B